Multiomics analysis reveals the mechanical stress-dependent changes in trabecular meshwork cytoskeletal-extracellular matrix interactions - Soundararajan, Avinash; Wang, Ting; Sundararajan, Rekha; Wijeratne, Aruna; Mosley, Amber; Harvey, Faith Christine; Bhattacharya, Sanjoy; Pattabiraman, Padmanabhan Paranji (Frontiers in Cell and Developmental Biology, 2022)
Trabecular meshwork (TM) tissue is subjected to constant mechanical stress due to the ocular pulse created by the cardiac cycle. This brings about alterations in the membrane lipids and associated cell-cell adhesion and cell-extracellular matrix (ECM) interactions triggering intracellular signaling responses to counter mechanical insults. A loss of such response can lead to elevated intraocular pressure (IOP), a major risk factor for primary open-angle glaucoma. The purpose of this study was to understand the changes in signaling responses by TM subjected to mechanical stretch. We utilized multiomics to perform an unbiased mRNA sequencing to identify changes in transcripts, mass spectrometry (MS)-based quantitative proteomics for protein changes, and multiple reaction monitoring (MRM) profiling-based MS and HPLC-based MS to characterize the lipid changes. We performed pathway analysis to obtain an integrated map of TM response to mechanical stretch. The human TM cells subjected to mechanical stretch demonstrated an upregulation of protein quality control, oxidative damage response, pro-autophagic signal, induction of anti-apoptotic, and survival signaling. We propose that mechanical stretch-induced lipid signaling via increased ceramide and sphingomyelin potentially contributes to increased TM stiffness through actin-cytoskeleton reorganization and profibrotic response. Interestingly, increased phospholipids and diacylglycerol due to mechanical stretch potentially enable cell membrane remodeling and changes in signaling pathways to alter cellular contractility. Overall, we propose the mechanistic interplay of macromolecules to bring about a concerted cellular response in TM cells to achieve mechanotransduction and IOP regulation when TM cells undergo mechanical stretch.